Curvularia lingshanensis sp. nov., a new pathogen causing stem and leaf rot on Curcuma kwangsiensis in China - Liang, Jinbiao; Wang, Hanyi; Wei, Rongchang; Zhou, Chunshui; Su, Jiali; Liu, Ze; Lin, Siyu; Guo, Jingyi; Gao, Qi; Zhou, Hao (Plant disease, 2025)
Curcuma kwangsiensis S. G. Lee et C. F. Liang, a medicinal plant in the Zingiberaceae family, is cultivated in southwestern China (Feng et al., 2022). In May 2021 and 2022, a stem and leaf rot disease in C. kwangsiensi was observed in Qinzhou and Nanning, Guangxi Province, with an incidence of approximately 15% across the survey area (0.5 ha). Initial symptoms included brown, water-soaked lesions on tender leaves, which progressed to involve entire leaves and stems, ultimately causing the plant to turn yellow, soft, and slimy, leading to plant death. To identify the pathogen, 29 Curvularia-like strains were obtained from six symptomatic plants using tissue isolation methods and single-spore purification (Zhang et al., 2013). The fungus was consistently isolated from all six plants. Five isolates were selected for further investigation. On potato dextrose agar (PDA), colonies were sparse and grey. On oatmeal agar (OA), colonies were cottony, with a green fruiting zone and a pale grey aging zone. On malt extract agar (MEA), colonies exhibited irregular edges with a raised whitish zone. Conidia were induced on water agar (WA). Conidiophores were erect, short, septate, unbranched, and measured 11.5~35 × 2.7~4.9 μm (n = 50). Conidiogenous cells proliferated terminally, sympodially, were slightly verruculose to smooth-walled, light brown, and measured 3.2~12.0 × 2.5~5.3 μm (n = 40). Conidia were straight or clavate, seldom curved at the third cell from the base, mostly three-septate, and occasionally two-septate, olivaceous brown, and measured 11.0~27.9 × 4.5~11.0 μm (n = 70). The internal transcribed spacer (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and elongation factor 1 alpha (EF-1α) loci were amplified using primers ITS1/ITS4 (White et al., 1990), GPD-1/GPD-2 (Berbee et al., 1999), and EF-983F/EF1-2128R (Carbone et al., 1999), respectively. The sequences were submitted to the GenBank. A phylogenetic analysis revealed that the five representative strains formed a distinct clade, separate from other known Curvularia species. They were closely related to C. radici-foliigena, C. radicicola, C. petersonii, and C. pseudoclavata (Marin-Felix et al., 2020; Raza et al., 2019; Tan et al., 2018), but differed in the characteristics of conidiophores, conidiogenous cells, and conidia. Based on morphology and multi-gene phylogeny, the pathogen was identified as C. lingshanensis sp. nov. To test pathogenicity, conidia from 2-week-old cultures of C. lingshanensis strain CK21.1 were resuspended to prepare conidial suspension (106 spores/mL). Six healthy 2-week-old C. kwangsiensi seedlings were used: three were sprayed with 2 mL conidial suspension, while the other three were treated with sterile water as controls. Inoculated plants were maintained in a greenhouse at 25°C with a 12-h photoperiod and approximately 90% humidity. Within 12 d, the C. kwangsiensi seedlings inoculated with CK21.1 conidia developed severe stem rot and water-soaked necrosis at the leaf base, resembling the symptoms observed in the field. No symptoms were observed in the controls. The experiments were repeated three times with consistent results. To fulfill Koch's postulates, C. lingshanensis was consistently re-isolated from necrotic tissues of all inoculated plants, whereas no fungal isolates were recovered from the controls. This study represents the first report of stem and leaf rot disease in C. kwangsiensi caused by a novel Curvularia species, C. lingshanensis.